2015
DOI: 10.1002/2014jc010609
|View full text |Cite
|
Sign up to set email alerts
|

Modeling long‐term change of planktonic ecosystems in the northern South China Sea and the upstream Kuroshio Current

Abstract: Field studies suggested that the biogeochemical settings and community structures are substantial different between the central Northern South China Sea (NSCS) and the upstream Kuroshio Current (KC). In particular, the water column of KC is characterized by substantially lower nutrients and productivity but higher Trichodesmium abundance and nitrogen fixation compared to the NSCS. The mechanism driving the difference of the two marine ecosystems, however, remains inadequately understood. Here, a onedimensional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 50 publications
6
35
0
Order By: Relevance
“…The vertical diffusion negatively influences the nitracline steepness. The modeled time series distributions of nitrate gradients and diffusive nitrate fluxes in the northern SCS and the upstream Kuroshio Current showed similar results (Li et al, 2015). Beckmann and Hense (2007) conducted a sensitivity analysis of both vertical diffusivity and nutrient concentration at the bottom boundary to examine the vertical phytoplankton and nutrient profiles in oligotrophic oceans, and their numerical results support the relations presented in Eq.…”
Section: Steepness Of the Nitraclinementioning
confidence: 52%
See 2 more Smart Citations
“…The vertical diffusion negatively influences the nitracline steepness. The modeled time series distributions of nitrate gradients and diffusive nitrate fluxes in the northern SCS and the upstream Kuroshio Current showed similar results (Li et al, 2015). Beckmann and Hense (2007) conducted a sensitivity analysis of both vertical diffusivity and nutrient concentration at the bottom boundary to examine the vertical phytoplankton and nutrient profiles in oligotrophic oceans, and their numerical results support the relations presented in Eq.…”
Section: Steepness Of the Nitraclinementioning
confidence: 52%
“…In some oligotrophic oceans, the SCML will be deeper than the SBML due to the effect of photoacclimation on the vertical distribution of chlorophyll (Fennel and Boss, 2003). For example, Li et al (2015) showed that the modeled maximum nitrate gradient (nitracline) occurred below the depth of the SCML in the northern SCS, and then we can deduce that the nitracline depth is also deeper than the depth of the SBML. In the Mediterranean Sea, Bahamón et al (2003) found that the nitracline occurred below the depth of the SCML at 88 % of the stations (50 out of 57 stations).…”
Section: Data Sourcesmentioning
confidence: 94%
See 1 more Smart Citation
“…Here we study the temporal variability of export production (EP) at a pelagic station of XS (Figure ) with a 1‐D physical‐biogeochemical coupling model (Li et al, ). We evaluate the model results by comparing them with the time series data of XS, including the satellite sea surface temperature (SST) and sea surface chlorophyll‐ a (SSChla) from January 2000 to December 2014, the IPP from January 2005 to December 2014, and the sinking POC flux by a moored sediment‐trap from August 2012 to September 2014.…”
Section: Introductionmentioning
confidence: 99%
“…(Tian et al, 2009;Liu and Lozovatsky, 2012;Yang et al, 2014). It was also suggested that phytoplankton blooms off the west coast of the nSCS could be induced by wind stress curl-driven upwelling during the spring inter-monsoon season (Wang and Tang, 2014), which would cause a local uplift of isopycnals leading to nutrient injection into the euphotic zone with subsequent changes of community structure and productivity (Rykaczewski and Checkley, 2008;Li et al, 2015). By modifying the surface wind stress and wind stress curl via air-sea coupling, the eddy-induced Ekman pumping (Gaube et al, 2013) was important for phytoplankton production in the nSCS during the inter-monsoon transition period (Lin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%